Effect of gastroenterology resident use of a social network workgroup on skills in characterizing colorectal neoplasia: Prospective study - Lafeuille, Pierre; Rivory, Jérôme; Héroin, Lucile; Gronier, Olivier; Couraud, Sébastien; Wallenhorst, Thimothee; Albouys, Jérémie; Legros, Romain; Sautereau, Denis; Chaussade, Stanislas; Ponchon, Thierry; Subtil, Fabien; Jacques, Jeremie; Pioche, Mathieu (Endoscopy International Open, 2025)
Accurate endoscopic characterization of colorectal lesions is essential for predicting histology but remains difficult. We studied the impact of a social network workgroup on level of characterization of colorectal lesions by gastroenterology residents.We prospectively involved residents who characterized 25 and 40 colorectal lesions in two different questionnaires over 1 year. Three groups were considered: regulars who were already part of the workgroup before the first evaluation, newcomers who joined in during evaluation, and reluctant who did not. Participants rated each lesion according to the CONECCT classification (hyperplastic polyp [IH], sessile serrated lesion [IS], adenoma [IIA], high-risk adenoma or superficial adenocarcinoma [IIC], borderline invasive adenocarcinoma [IIC+], or deeply invasive adenocarcinoma [III]) and their progression score over 1 year was assessed. Correct histological status was defined by pathology reports or combined criteria between histology and expert opinion for high-risk adenoma or adenocarcinoma.Of the 117 participants, 82.9% completed the two questionnaires, with 16.5% regulars, 71.1% newcomers, and 12.4% reluctant. For similar starting levels, progression in characterization was +2 (95% confidence interval [CI] 1–3; P <0.001) for newcomers and +2 (95% CI –0.5–4); P = 0.122) for reluctant. The regulars had a higher starting level with a +0.5 (95% CI –2 to 2; P = 0.691) progression score.Gastroenterology resident 1-year use of a social network workgroup does not improve their skills in characterizing colorectal neoplasia. Further intensive training is needed to improve the characterization level of gastroenterology residents.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; Colorectal cancer; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE...); Quality and logistical aspects; Training